A Functional Role for the Epigenetic Regulator ING1 in Activity-induced Gene Expression in Primary Cortical Neurons. (15th January 2018) - Leighton, Laura J.; Zhao, Qiongyi; Li, Xiang; Dai, Chuanyang; Marshall, Paul R.; Liu, Sha; Wang, Yi; Zajaczkowski, Esmi L.; Khandelwal, Nitin; Kumar, Arvind; Bredy, Timothy W.; Wei, Wei
Highlights: Neuronal activation alters genome-wide deposition of the epigenetic regulator ING1. ING1 knockdown decreases expression of genes related to synaptic plasticity. PIWIL1 and PIWIL2 are upstream of ING1 in neuronal gene regulation. Abstract: Epigenetic regulation of activity-induced gene expression involves multiple levels of molecular interaction, including histone and DNA modifications, as well as mechanisms of DNA repair. Here we demonstrate that the genome-wide deposition of inhibitor of growth family member 1 (ING1), which is a central epigenetic regulatory protein, is dynamically regulated in response to activity in primary cortical neurons. ING1 knockdown leads to decreased expression of genes related to synaptic plasticity, including the regulatory subunit of calcineurin, Ppp3r1. In addition, ING1 binding at a site upstream of the transcription start site (TSS) of Ppp3r1 depends on yet another group of neuroepigenetic regulatory proteins, the Piwi-like family, which are also involved in DNA repair. These findings provide new insight into a novel mode of activity-induced gene expression, which involves the interaction between different epigenetic regulatory mechanisms traditionally associated with gene repression and DNA repair.